Tensile and Bending Analysis of Composite Material - Ashish Saraswat, Premanand S. Chauhan, Avadesh K Sharma , Prem Prakash Pandit (International Journal of Advanced Science and Technology, 2020)
Composite materials are extensively used in constructing components of various applications due to its high strengthen property in comparison of any isotropic materials. Composite materials can be characterized as the subsequent material from the blend of, at least two, unique materials. The result of their blend is a material that joins their individual attributes, giving the composite one of a kind and intriguing properties. In this study, tensile and flexural test were done on E-glass used with epoxy hardener composite material. The tensile property of specimen composite material was taken in accordance with ASTM standard D-638 in shape of dog-bone and flexural properties of specimen of same material was taken in accordance with ASTM standard D-790 in rectangular shape. The results show that on using E-glass with Epoxy hardener having higher tensile and flexural strengths as compared to steel grade material. This material can be used in various engineering applications.